Performance of Indonesia Sharia companies: Does corporate ethical identity matter? - Irma Hartyanti; Puji Harto; Chutima Wangbenmad (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - The development of Islamic finance has made many Indonesia sharia companies register themselves as part of the Indonesia Sharia Stock Index (ISSI). The government always encourages sharia economic growth that upholds ethics. From the Islamic perspective, ethics is the foundation of all aspects of life. This study aims to analyze the performance of Indonesia sharia companies, by linking the importance of Corporate Ethical Identity (CEI) which is implemented in corporate culture.Method - Quantitative research is reviewed through the annual reports of manufacturing companies registered at ISSI for the 2018 and 2019. Linear regression analysis, along with moderated regression analytics, was used to analyze data from 154 manufacturing companies.Result - The results of the study show that CEI has a positive influence on firm performance, and ownership structure as a moderating variable strengthens the influence of CEI on firm performance.Implication - Sharia companies in Indonesia are advised to increase CEI reporting so as to improve financial performance in accordance with sharia principles.Originality - This study represents the inaugural investigation into CEI within Islamic companies operating in Indonesia, with a specific emphasis on corporate culture. The novelty in this research is the focus on company culture, and what distinguishes it from the mentioned study is the utilization of the ownership structure concept as a moderating variable. It also incorporates the utilization of the ownership structure concept as a moderating variable.